Engajamento parental e valores humanos: o poder mediador da satisfação parental - Machado, Mayara de Oliveira Silva (2020)
This present thesis attempted to test a model of mediation, using parental satisfaction as the mediator of the relationship between parental engagement and human values. For this purpose, it was carried out in two studies. Study 1 aimed to collect evidence of validation and accuracy for both the Parental Engagement Scale (PES) and the Parent Satisfaction Scale (PSS). 226 Parent residents of various Brazilian States answered the PES, the PSS, and sociodemographic questions. Majority from Paraíba (66.8%), women (57.5%), married or in Common Law marriage (86.3%), average age of 37.47 years old (SD = 7.92, amplitude of 19 to 60 years old), minimum of one child aged between 5 to 12 years old (M = 8.89; SD = 7.65). The exploratory factorial analysis, using HULL and MAP as criteria, suggested a onedimensional supporting validly and accuracy for PES (Cronbach's alpha and McDonalds' Omega = 0.87) and for PSS (Cronbach's alpha and McDonalds' Omega = 0.82). Study 2 set out to ascertain PES and PSS structures extracted in the Study 1, to verify the contribution of sociodemographic variables in the explanation of parental engagement and parental satisfaction, to identify the pattern between the sub-functional values of parental satisfaction and parental engagement, and, finally, to test a mediation model of parental engagement. This time 204 parent residents in Paraíba, with a majority of women (88.6%), married or in Common Law marriage (77.3%), average aged around 35.10 years old (SD = 7.00, amplitude of 23 to 58 years old), with at least one child aged between 5 to 12 years old (M = 8.89; SD = 7.65). They presented an average of 3.54 (SD = 0.68) in the assessment of the marital relationship and 3.81 (SD = 0.46) in the self-assessment as a father/mother. The respondents answered the questionnaire from Study 1 aided by the Basic Values Survey. From the results of confirmatory factor analysis, it was possible to confirm a one-factor structure for PES [χ²/ gl = 1.91, GFI = 0.91, CFI= 0.91 RMSEA = 0.07 (CI 90% = 0.05 – 0.08), with Cronbach's alpha = 0.82, and composite reliability (CR) of 0.83. For the PSS [χ²/gl = 3.58, GFI = 0.97, CFI = 0.94, RMSEA = 0.07 (CI 90% = 0.05 – 0.08), with Cronbach's alpha = 0.75, and composite reliability (CR) of 0.77. Subsequently, through Pearson’s correlation followed by linear regressions, it was possible to verify that the evaluation of the marital relationship and the self-evaluation as a parent were the best predictors of parental engagement and parental satisfaction, and the number of children as a predictor parental engagement, although in the negative direction. One can also identify positive and statistically significant relationships (p <0.05) between parental satisfaction and parental engagement, in addition to the evaluative sub-functions (Interactive, Normative, Suprapersonal, Existence and Promotion), with both variables mentioned above. Then, through linear regressions (simple and multiple), parental satisfaction (β = 0.66; p <0.001) and the evaluative sub-functions (normative, β = 0.20; p <0.05; and promotion, β = 0.20; p <0.05), and as a predictor of parental satisfaction the normative sub-function (β = 0.26; p <0.001). It was observed, then, that the sub-function promotion did not have a predictive power in parental satisfaction, for this reason, we opted to exclude it from the model. Then, a mediation model was tested considering parental engagement as a criterion variable, normative sub-function as an independent variable and parental satisfaction as a mediator, whose results showed a total mediation, since that, in the presence of parental satisfaction, the direct effects between the normative sub function and parental engagement are no longer significant (λ = 0.09; p = 0.07; CI 90% = 0.01 / 0.18). Thus, people who prioritize the normative sub-function are more engaged in their parental functions because they have higher levels of parental satisfaction. Thereby, it is believed that human values and parental satisfaction are configured as important variables in promoting parental engagement. Thus, the study contributes to Social Psychology, especially with regard to family relationships, since it seeks to explain parental 13 engagement. This thesis therefore, collaborates with the scientific advancement of the theme, providing empirical data that instigate reflection on the possibilities of interventions in parental relationships in order to obtain positive experiences in the lives of parents and children.